1999
DOI: 10.1097/00004479-199910000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Screening among Community Health Center Women: Eliminating the Gaps

Abstract: CHCs are providing access to Pap smear testing, mammography, and clinical breast examination for women who are at an increased risk for morbidity and mortality associated with cancers of the cervix and breast. A higher proportion of CHC women of most racial and ethnic groups and women below poverty level are up to date on cancer screening than comparison groups. In most cases, CHC women meet or exceed the Healthy People 2000 objectives for the nation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…In addition, women of color— particularly Black women—are more likely to use community- based health clinics and family planning clinics that offer free or reduced cost Pap tests, 56 and where women are more likely to be up- to-date on their screenings. 57 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, women of color— particularly Black women—are more likely to use community- based health clinics and family planning clinics that offer free or reduced cost Pap tests, 56 and where women are more likely to be up- to-date on their screenings. 57 …”
Section: Discussionmentioning
confidence: 99%
“…This emphasizes the importance of the results found in this study and indicates a potential approach to reduce disparity. Other studies that have not found significant differences between racial/ethnic groups in health care [33][34][35][36] have either relied on patient survey data, 35,36 one health care procedure, 35 one payer type, 33 or a very small patient sample. It was hypothesized that America's urban safety net system might have achieved amelioration disparity for at least some outcomes given that these institutions have previously addressed a number of the issues which are believed to contribute to such disparity.…”
Section: Discussionmentioning
confidence: 99%
“…Minority women including those who are black or Hispanic are more likely than non-Hispanic white women to seek care from outpatient departments [8,9]. Many primary care visits occur in physicians offices and in HMOs, including for population subgroups such as racial minorities and Hispanic women.…”
Section: Discussionmentioning
confidence: 99%
“…However, community health centers and hospital OPDs are also important providers of primary health care for many women including those who are recent immigrants to the United States [9,10]. Prior studies have shown that the women seen at community health centers are more likely to be up to date for breast cancer screening tests than low-income women in the general population [8]. The rates of recent CBE observed in this study were only slightly lower among women who reported they received routine health care at a clinic or health center, or hospital OPD, as compared with those who received health care at a doctor's office or HMO, and differences did not persist after adjustment for other factors.…”
Section: Discussionmentioning
confidence: 99%